Improved modified reputation-base trust for wireless sensor networks security - Alkalbani, Abdullah Said; Mantoro, Teddy; Md Tap, Abu Osman (Indian Society for Education and Environment, 2016)
Background/Objectives: Trust, reputation and power resources limits of WSNs are active matters. In this paper Modified Reputation Based-Trust Mechanism (MRT) enhanced to minimize power consumption and increase privacy at the same time. Methods/Statistical analysis: Two security testing threats considered during simulation of proposed trust and reputation model in order to evaluate model efficiency and trustworthy. The first testing threat has to do with the oscillating behavior of the pernicious nodes offering the required service. The another threat applied contains of the possibility for the malicious nodes to sort a collusion through themselves. Findings: Simulation results prove limited energy consumption and enhancement is security better than previous studies. Application/Improvements: Proposed mechanism has security strengths against malicious nodes with oscillating and collusion effects. Results prove that its remains malleable to high percentages of malicious servers when the percentage of client sensors are greater than 60%.